Zur Gliederung, Bildung und Altersstellung des Kalksteinschutts am Trauf der westlichen Schwäbischen Alb - D. Weippert (Eiszeitalter und Gegenwart, 1960)
The steep slope to the NW of the Schwäbische Alb, the Albtrauf, is covered with thick layers consisting of limestone pebbles and cobbles. Because of the difference in grain size and in the percentage of loam, sand and silt mixed in, we can distinguish several different types of rubble: the pieces of the mountain screes, the „coarse rubble" an the „fine rubble". The „coarse rubble" and the „fine rubble" came into being during the Würm-glaciation. At the same time, they were transported by solifluction and spread all over the Albtrauf. The mountain screes are supposed to have been formed only in the postglacial area. The formation of the „fine rubble" did not appear before the time, where the ice reached its greatest extent. At some places, the „fine rubble“ arose „in situ" from formerly „coarse rubble". This has been proved by many profiles and by the extent and depth of the cryoturbated involutions found there.